The International Criminal Court in the Context of International Criminal Law - Kovács, Péter (International Law From A Central European Perspective, 2022)
There was a long path to the establishment of a permanent international criminal tribunal, from 1474 through the so-called Versailles Peace Treaties, the International Military Tribunal of Nuremberg and the International Military Tribunal of Tokyo, and the adoption of the Convention on the Prevention and Punishment of the Crime of Genocide to the text of the Rome Statute, which was adopted in 1998. Although the circle of international crimes is much larger than that of the crimes covered by the Rome Statute, it cannot be denied that it covers most international crimes. The jurisdiction of the International Criminal Court is based on the satisfaction of the preconditions settled in the Rome Statute. The jurisdictional competence of the International Criminal Court is based on two hypotheses: It is competent when the crime is committed on the territory of a States Party to the Rome Statute or by a national of a States Party. The main organs of the International Criminal Court are the Judiciary, the Office of the Prosecutor, the Registry, and the Assembly of States Parties. The International Criminal Court must use different evidentiary standards when rendering its decisions.KEYWORDS: Rome Statue, international crimes, jurisdictional competence, evidentiary standards